The Use of Alphabet Box Media in Letter Recognition in Children Aged 4-5 Years La Consolacion School Larantuka Kindergarten - selvana yosefa sabu balun; Ria Anggun Trisyani (Early Childhood Education Development and Studies (ECEDS), 2022)
The purpose of this classroom action research is to find out the increase in the ability to recognize letters through alphabet box media games in group A children at La Consolacion School Kindergarten in 2022/2023. The research subjects were group A La Consolacion School Larantuka Kindergarten in the 2022/2023 school year, which consisted of 10 children and consisted of 4 boys and 6 girls with an average age of 4 years. This research was conducted in group A TK La Consolacion School, Sarotari village, Larantuka subdistrict, East Flores district, where the researcher was assigned. This research was conducted using two cycles, with each cycle holding 3 meetings. This research was conducted for approximately 3 weeks. Based on the results of the study, it can be concluded that the Application of Alphabetic Media can improve the ability to recognize letters in children aged 4-5 years. Teachers should be more creative in classroom learning, especially in learning media so that they can optimally improve children's language skills. Keywords: ability, language, alphabet box